Theoretical Analysis Of Friction Compensation Using Sliding Mode Control - Rafan, Nur Aidawaty; Jamaludin, Zamberi; Tjahjowidodo, Tegoeh; Chey, Long Sheng; Chiew, Tsung Heng (Trans Tech Publications, Switzerland, 2012)
Friction is an undesired nonlinear phenomenon that reduces position and tracking accuracy in machine tools application. This paper focuses on development of control technique to compensate friction force at motion reversal of a drive system that generates quadrant glitch phenomenon thus improving tracking accuracy. Sliding Mode Control (SMC) is designed to compensate friction. The Generalized Maxwell-Slip (GMS) friction model is applied for numerical analysis. The performance of the controller is analysed based on the reduction in the quadrant glitches magnitude. The performance of the SMC controller is compared with the classical PID controller. Results show that SMC controller yields the smallest quadrant glitch magnitudes.